DEVELOPMENT THROUGH ICT: EXPLORING THE USE OF JOB SEARCH APPLICATION CAREER - Dini Fitriani, Ajeng (Journal of English Education and Teacher Trainer, 2024)
The aim of this study is to analyze the effectiveness of job search applications in supporting individual career development through ICT. The study uses a qualitative-descriptive mini research approach, with a separate interview with fresh graduates from State Islamic University Sunan Gunung Djati Bandung. The results of the study show that job search applications can be an effective tool for fresh graduates in their career development and job search. The applications can help them to connect with potential employers, learn about different companies and industries, and prepare for job interviews. However, the study also found that some fresh graduates are not aware of the benefits of job search applications, and that some applications are not as effective as others. The study concludes that job search applications can be a valuable tool for fresh graduates, but that it is important to choose the right applications and to use them effectively.